An Evaluation of Extension Activities Organized Under FLD on Oilseeds and Pulses in KVKs of Punjab and J&K States - Dar , M. A.; Alam, Safeer; Kumar, Sushil (Indian Journal of Extension Education, 2017)
Various extension activities were organized by the KVKs of J&K and Punjab states to maintain linkage with the farmers,  research and developmental agencies. The linkages help in continuous refinement of technology and provide feedback to  research system. A sample of 200 FLD farmers were selected randomly on proportional allocation from two states of  northern india i.e. J&K and Punjab covering two KVKs from each states. The FLD farmers were personally interviewed  with the help of pre-structured schedule. The results revealed that overall percentage of farmers attended field days in  Punjab was 80.82 as against 47.69 per cent in J & K, whereas Kisan Mela is concerned, 79.94 and 70.81 per cent of farmers  participated in Punjab and J & K respectively. In case of printed literatures, only 20.54 per cent farmers in J & K and 36.43  per cent in Punjab reported that printed materials were distributed to FLDs farmers. It was also observed that 61.49 per  cent farmers in Punjab and 47.69 per cent in J & K attended trainings and group discussions conducted during FLD  programme. Thus it may be concluded that more number of farmers in Punjab had participated in extension activities  organized under FLD programmes such as field days, Kisan Melas, trainings and group discussions as compared to J & K.
Keywords: KVKs; FLD; field -days; kisan mela; trainings